REVEALING DIFFICULTIES AND CAUSING FACTORS HINDERING STUDENT’S IN SPEAKING ENGLISH - Imananda Akmal Dharmawan (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Speaking skill is widely considered as the skill that indicates individual’s proficiency in a language. Despite of its importance, speaking skill is not easy to master, as it involves many competencies in pronunciation, lexical, grammatical and semantic elements that causes difficulties in speaking English. Therefore, it is essential to identify English speaking difficulties and its factors that encountered by EFL learners This study carried out descriptive qualitative research method and online semi structured interview as instrument. The data for this research collected from 5 students of English department from University of Islam Malang through the use of WhatsApp voice note. The data are analyzed using qualitative data analysis that consist of data reduction, grouping, coding, display and interpretation. The result finds eight difficulties and ten factors that causes those difficulties in speaking English language. The data also shows that one difficulty can be caused by different factors like nervous related difficulties can be caused by speaking partner and being afraid of mistakes, moreover, one factor are identified to be the causes of many difficulties such as vocabulary that causes many difficulties in speaking. It suggested to understand the speaking problems along with the cause for the students to find solution and anticipation of the speaking problems.Key Words: English speaking skill, difficulties, factors.